Geometric transformation and cultural values in traditional batik of Banyumas and Pekalongan: An ethnomathematics study - Kusno, Kusno; Gunawan; Nalim; Eka Setyaningsih; Furqon, Miftahul; Faiz, Mohd (Universitas Hamzanwadi, 2025)
Banyumas and Pekalongan batik are local cultural heritages of Central Java that contain philosophical values, regional identity, and geometric patterns. Although batik has been widely known as a uniform, its use as a medium for learning mathematics, especially transformation geometry, is still limited. This study aims to examine the relationship between Banyumas and Pekalongan batik motifs with the concept of transformation geometry and the cultural values ​​contained. A qualitative approach with ethnographic methods was used through observation, documentation, in-depth interviews, and field notes. The subjects of the study included cultural figures, batik craftsmen, and tour guides at the Anto Jamil Batik Center (Banyumas) and the Pekalongan Batik Museum. The study focused on the Jahe Srimpang and Babon Angrem motifs (Banyumas), as well as Jlamprang Gunungan and Jlamprang Seamless (Pekalongan). The results showed that these motifs contain elements of geometric transformation such as translation, rotation, symmetry, reflection, and dilation. This study recommends the use of batik as a source of mathematics learning based on local wisdom.